FREE RADICAL SCAVENGING ACTIVITY OF MARINE SPONGES COLLECTED FROM KOVALAM, CHENNAI - Thambidurai, Yuvarani; D, Sudarsanam; Skm, Habeeb; T, Ashok Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The main focus of this study is to screen the marine sponges for potent free radical scavenging activity. Methods: Various methods such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assay are employed to ascertain the antioxidant properties of marine sponges namely Dysidea herbacea and Sigmadocia pumila. Results: On analyzing, the result of ABTS assay D. herbacea and S. pumila exhibited almost equal antioxidant properties. While calculating the inhibitory concentration 50% value for DPPH assay, the Sample 1 and 2 has an IC of 655.49 and 826.739 Î¼l, respectively, and in FRAP assay, the Sample 1 and 2 has an IC of 67.587 and 74.57 Î¼g, respectively. Conclusion: Overall from this assay, D. herbacea revealed slightly better antioxidant activity when compared to S. pumila, also which in future may serve as a better source to fight against various diseases